The Predictive Validity of the Structured Assessment of Violence Risk in Youth for Young Spanish Offenders - Ortega-Campos, Elena; García-García, Juan; Zaldívar-Basurto, Flor (Frontiers in Psychology, 2017)
Abstract The present study examined the predictive validity of the SAVRY in a group of young Spanish offenders. The sample is made up of 594 minors from the Juvenile Court, between the ages of 14 and 18 at the time they committed the delinquent act. The SAVRY was able to differentiate between low and high-risk younger offenders. Mean scores on risk factor are greater in the group of recidivist offenders, the group of non recidivist shows higher mean scores in Protective domain. The accuracy of the instrument is high (AUC Risk Total Score = .737 and AUC Summary Risk Rating = .748). An approximation of the predictive validity study of the SAVRY in Spanish younger offenders is presented. The results obtained support the SAVRY good functioning with not English samples.